Accuracy of MRI for Diagnosis of Acute Invasive Fungal Sinusitis Taking Histopathology as a Gold Standard - Maham Abid, Nayab Asif, Mehwish Tahir, Maimoona Gulshan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Diagnostic accuracy of MRI for diagnosis of acute invasive fungal sinusitis by taking histopathology as gold standard Study design: Cross sectional study at Radiology department, Ittefaq Hospital Lahore Duration: Six months from 23-02-2018 to 23-08-2018 A total of 346 cases fulfilling inclusion & exclusion criteria were taken. All cases were done MRI procedure. Histopathology reports were also obtained. The results obtained were used to calculate the diagnostic accuracy. Results: The male were 195(56.4%) and female were 151(43.6%). On histopathology, 120(34.7%) cases showed positive results. By MRI study, 114(32.9%) cases were of positive finding. The sensitivity, specificity, positive and negative predictive value of MRI was 90%, 97.4%, 94.7% and 94.8% respectively and diagnostic accuracy of MRI was 94.8%. Conclusion: For diagnosing acute invasive fungal sinusitis, there is high diagnostic accuracy of MRI taking histopathology as gold standard. Keywords: sinus fungal infection, histopathology, MRI